Individual-typological features of youth involved in physical and sports leisure activities - Pashchenko L.G. ,; Volkov L.A. , (Theory and Practice of Physical Culture, 2024)
Objective of the study was to identify the individual typological characteristics of young people who systematically engage in a certain type of physical education and sports leisure activity in the open air. Methods and structure of the study. The survey was attended by 60 young residents of Nizhnevartovsk, Khanty-Mansi Autonomous Okrug-Yugra, who spend their free time outdoors: workout, football, volleyball, walking or running, as well as participants in open fitness training. G. Eysenck's personality questionnaire was used to study individual psychological personality traits. To identify the factors of youth involvement in independently organized physical culture and sports activities, the author’s questionnaire was used. Results and conclusions. Among those who prefer workout classes, walking and running, introverts predominate. High levels of extraversion were found in individuals who chose team sports. Open street fitness training brought together young people with different psychodynamic characteristics and temperament types. A relationship was found between the choice of the form of participation in mass physical culture and sports events with the type of temperament and indicators of extraversion/introversion. The results obtained indicate the importance of scientific psychological and pedagogical support for physical education and sports activities of young people who independently organize their leisure time in the open air.